Human-mediated outdoor genome editing is not possible so therefore poses no risk to the environment - Andrew C. Allan; Barry Scott; Warren Tate; Paula E. Jameson; Elspeth MacRae; Anthony J. Conner; Revel Drummond; Alec Foster; Cathie Martin; John Caradus (Ecotoxicology and Environmental Safety)
There is a world-wide re-examination of the regulations that surround genetic technologies, including gene edited organisms. In many countries, crop plants with small gene edits and where no foreign DNA is introduced are exempt from detailed regulatory assessment. This will allow these types of plants to be released, after assessment for benefit and risk, by plant breeders or plant scientists. The full regulatory risk assessment and risk management of novel (including transgenic) plants is well established and focusses on five key criteria (weediness, gene flow, plant pests, non-target impact, biodiversity). However, plants produced by “traditional” plant breeding technologies, many of which have been subject to random mutagenesis or wide crosses that may introduce enormous numbers of DNA changes, are almost never considered novel so are not assessed for risk through a regulatory system. The most targeted, versatile and widely used gene editing technique involves the enzyme-RNA complex, CRISPR-Cas. This method can produce far more precise and targeted changes than “traditional” mutagenesis techniques. Getting the CRISPR-Cas machinery into plant or animal cells requires highly sterile tissue culture and sophisticated delivery tools. Therefore, gene editing, in the open environment by “field spraying”, is not currently possible. While other uses of nucleotide chemistry – such as double stranded RNA - have been applied to plants to knock down gene expression, this is not gene editing and produces no DNA change. Suggestions that gene editing using CRISPR-Cas can occur through spraying directly on to plants in the outside environment is fanciful, incorrect and misleading.